2008
DOI: 10.1007/s12041-008-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs (miRNA) in circadian rhythmicity

Abstract: MicroRNA (miRNA) is a recently discovered new class of small RNA molecules that have a significant role in regulating gene and protein expression. These small RNAs (∼22 nt) bind to 3 untranslated regions (3 UTRs) and induce degradation or repression of translation of their mRNA targets. Hundreds of miRNAs have been identified in various organisms and have been shown to play a significant role in development and normal cell functioning. Recently, a few studies have suggested that miRNAs may be an important regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 75 publications
3
29
0
2
Order By: Relevance
“…Up to now, researchers have made many attempts to identify clock-associated miRNAs and their function in the circadian rhythm (Pegoraro and Tauber, 2008). Cheng et al have revealed that miR-219 and miR-132 were shown to regulate the circadian clock in the mouse suprachiasmatic nucleus (Cheng et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, researchers have made many attempts to identify clock-associated miRNAs and their function in the circadian rhythm (Pegoraro and Tauber, 2008). Cheng et al have revealed that miR-219 and miR-132 were shown to regulate the circadian clock in the mouse suprachiasmatic nucleus (Cheng et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Xbsx could be continuously transcribed, but inhibitory factors present during the daytime might degrade or destabilize its mRNA. Putative inhibitory factors could be represented by rhythmically expressed deadenilases (similar to Nocturnin but with an opposite phase of expression) (23) and micro-RNAs (24).…”
Section: Xbsx Is Expressed In a Cyclical Manner In Pineal Photoreceptormentioning
confidence: 99%
“…MicroRNAs were also identified as molecular elements that help in the regulation of the circadian machine (178,179).…”
Section: Connecting the Whole Tale: Mrna Surveillance Under Differentmentioning
confidence: 99%